1996
DOI: 10.1080/10408399609527725
|View full text |Cite
|
Sign up to set email alerts
|

Fish flavor

Abstract: This article reviews features of flavor in three groups of fishes and summarizes them as follows: (1) fresh saltwater fish are nearly odorless because they contain a small quantity of volatiles; (2 freshwater fish give off pyrrolidine and earthy-odor compounds, which are responsible for their maturity and surrounding water pollution, and (3) euryhaline fish exhibit a variety of unsaturated carbonyls and alcohols derived from enzymatic and nonenzymatic oxidation of polyunsaturated fatty acids (PAs). These featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
0
32

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(196 citation statements)
references
References 90 publications
11
153
0
32
Order By: Relevance
“…Secara amnya, ikan air tawar dikenali melalui sifat fi zikalnya yang berbau hanyir. Hal ini kerana, ikan jenis ini membebaskan sejenis bahan iaitu pyrrolidine dan bahanbahan yang berbau tanah yang memberi kesan kepada tahap kematangan ikan dan pencemaran air (Kawai & Sakaguchi 1996). Ikan air tawar yang biasa terdapat di pasaran adalah seperti tilapia hitam, tilapia merah, keli, belut, patin, toman dan baung.…”
Section: Pendahuluanunclassified
“…Secara amnya, ikan air tawar dikenali melalui sifat fi zikalnya yang berbau hanyir. Hal ini kerana, ikan jenis ini membebaskan sejenis bahan iaitu pyrrolidine dan bahanbahan yang berbau tanah yang memberi kesan kepada tahap kematangan ikan dan pencemaran air (Kawai & Sakaguchi 1996). Ikan air tawar yang biasa terdapat di pasaran adalah seperti tilapia hitam, tilapia merah, keli, belut, patin, toman dan baung.…”
Section: Pendahuluanunclassified
“…Acetaldehyde can be formed from the oxidized product of eicosapentaenoic acid via α/β double-bonded hydration and retro-aldol condensation (Kawai, 1996;Duflos et al, 2006).…”
Section: Tvb-n and Sensory Evaluationmentioning
confidence: 99%
“…The taste active constituents, which are generally non-volatile compounds, such as free amino acids, nucleotides, sugars, mineral salts, etc., have attracted considerable attention and their importance to seafood flavor is well document (14)(15)(16)(17)(18)(19)(20)(21). Several excellent reviews have also been reported on the subject of seafood flavor (7 7, 19\ 22-34).…”
Section: Flavor Of Seafoodsmentioning
confidence: 99%